Physiological hypoxia prevents bile salt‐induced apoptosis in human and rat hepatocytes. (20th November 2013) - Hohenester, Simon; Vennegeerts, Timo; Wagner, Michaela; Wimmer, Ralf; Drolle, Heidrun; Rieger, Christina; Denk, Gerald U.; Rust, Christian; Fiegl, Michael
Abstract Background & Aims Hydrophobic bile salts such as glycochenodeoxycholate (GCDC) accumulate in cholestatic liver disease and induce hepatocellular apoptosis, promoting profibrotic signalling. The tissue microenvironment is an integral player in cellular pathophysiology, but it is not routinely incorporated into laboratory studies. Tissue oxygen partial pressure (pO2) may be an underestimated component of the microenvironment: in the liver, a pO2 of 30–45 mmHg (approximately 6% O2) is physiological, because of predominant portal blood supply. It was the aim of this project to investigate the impact of physiological hypoxia (i.e. 6% O2) on hepatocellular function, namely, bile salt‐induced apoptosis. Methods Human hepatoma cells (HepG2‐Ntcp) and primary rat hepatocytes were cultured at standard laboratory (hyperoxic) conditions (21% O2) and at physiological hypoxia (6% O2) in parallel for 1–8 days to study hepatocellular apoptosis and activation of signalling pathways. Standard laboratory analyses were applied for bile salt uptake, caspase‐3/‐7 activity, western blotting and gene‐array analysis. Results Culturing at physiological hypoxia protected both human and rat hepatocytes against GCDC‐induced apoptosis: caspase‐3/‐7 activation was diminished by 3.1 ± 0.5‐fold in human HepG2‐Ntcp and completely abolished in primary rat hepatocytes. Bile salt uptake was unaffected. Induction of hypoxia‐inducible factor‐1α indicated adaption to physiological hypoxia. The MEK/ERK cascade was activated and anti‐apoptotic mediators were induced: N‐Myc down‐regulated gene, gelsolin and carbonic anhydrase IX were upregulated 12.4‐, 6.5‐ and 5.2‐fold respectively. Conclusions We conclude from these data that (i) physiological hypoxia protects hepatocytes from bile salt‐induced apoptosis, (ii) tissue pO2 is a crucial, underestimated component of the microenvironment and should (iii) be considered when studying hepatocellular physiology in vitro.